Liver impairment and medical management of Cushing syndrome and MACS - Minasyan, Mari; Suchy, Wiktoria; Fedak, Andrzej; Gamrat-Żmuda, Aleksandra; Hubalewska-Dydejczyk, Alicja; Valassi, Elena; Gilis-Januszewska, Aleksandra (Frontiers in Endocrinology, 2025)
Cushing syndrome (CS) and mild autonomous cortisol secretion syndrome (MACS) are states of endogenous hypercortisolemia, associated with multiple metabolic complications. The data on the impact of cortisol on the liver are inconsistent at times. From one perspective, some studies proved hepatotoxic cortisol action. Elevated liver enzymes and liver steatosis are common findings in patients with newly diagnosed CS and MACS (liver steatosis prevalence: 20%–66% and 25%–57%, respectively). Normocortisolemic subjects with liver steatosis/metabolic-associated steatohepatitis seem to have higher cortisol concentration than the healthy population. In contrast, other studies suggest that the liver impairment prevalence in hypercortisolemic patients with so many metabolic comorbidities would be expected to be much higher than it is reported. They postulate anti-inflammatory cortisol action as a preventive factor for liver disease progression in subjects with CS and MACS. The data on the hepatic safety profile of hypercortisolemia pharmacotherapy seems to be conflicting at times. Antihypercortisolemic medical therapy can potentially cause liver impairment; therefore, implementing the treatment of hypercortisolemia is often challenging in patients with liver dysfunction. We present two CS cases with baseline liver impairment, which improved on the treatment with steroidogenesis inhibitors. The case reports are followed by literature review regarding liver dysfunction in endogenous hypercortisolemia, impact of hypothalamic–pituitary–adrenal axis on the liver, and liver safety profile of medical treatment used in endogenous hypercortisolemia.